Analisis Pencapaian Aspek Pemberdayaan Pada Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan - Faisal Nomaini (Jurnal Empirika, 2018)
The community empowerment has become the basis of various government programs in the past 10 years. This research basically aimed to determine how the achievement of empowerment aspect indeed as the main goal in a community empowerment program. The community empowerment program under study was the implementation of the National Program for Empowerment of the Independent Rural Communities (PNPM-MP). This was a quantitative study by measuring the achievement of empowerment aspect from PNPM-MP activity in which the locus was in Lorok Village, Ogan Ilir Regency. The sample of this study was 80 respondents. The research questionnaire consisted of 36 statement items that had been through the validity and reliability tests of research instruments. The results showed that four of the five dimensions in the community empowerment variable in the PNPM-MP activities achieved low achievement. The dimensions of enabling, empowering, supporting and fostering are dimensions that achieved low achievement while the securing dimension achieved moderate achievement. This result was in line with the measurement of the overall empowerment variables in the implementation of PNPM-MP in Lorok Village of Ogan Ilir Regency with low achievement that is in percentage of 37%. It is concluded that the implementation of the program / activity of empowerment that took place efficiently and continuously in this village was not directly proportional to the increasing aspects of community empowerment.